Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2000
DOI: 10.1145/332040.332479
|View full text |Cite
|
Sign up to set email alerts
|

Using a large projection screen as an alternative to head-mounted displays for virtual environments

Abstract: Head-mounted displays for virtual environments facilitate an immersive experience that seems more real than an experience provided by a desk-top monitor [18]; however, the cost of head-mounted displays can prohibit their use. An empirical study was conducted investigating differences in spatial knowledge learned for a virtual environment presented in three viewing conditions: head-mounted display, large projection screen, and desk-top monitor. Participants in each condition were asked to reproduce their cognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(68 citation statements)
references
References 20 publications
0
66
2
Order By: Relevance
“…The error bars represent standard errors of the mean studies in the literature did not find an advantage in large display conditions (Gamberini, 2000;Tan et al, 2006;Tan, Gergle, Scupelli, & Pausch, 2004), some even finding a significant advantage with a standard desktop monitor (Czerwinski et al, 2002;Gamberini, 2000). There is also evidence showing that large displays can be helpful when using other types of virtual navigation tasks (Patrick et al, 2000;Tan et al, 2004;Tyndiuk, Lespinet-Najib, Thomas, & Schlick, 2007). For example, Tan et al (2004) found that large displays enhance performance in a path integration task, in which participants are led along two legs of a triangle and are asked to go back to the start position of the triangle.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The error bars represent standard errors of the mean studies in the literature did not find an advantage in large display conditions (Gamberini, 2000;Tan et al, 2006;Tan, Gergle, Scupelli, & Pausch, 2004), some even finding a significant advantage with a standard desktop monitor (Czerwinski et al, 2002;Gamberini, 2000). There is also evidence showing that large displays can be helpful when using other types of virtual navigation tasks (Patrick et al, 2000;Tan et al, 2004;Tyndiuk, Lespinet-Najib, Thomas, & Schlick, 2007). For example, Tan et al (2004) found that large displays enhance performance in a path integration task, in which participants are led along two legs of a triangle and are asked to go back to the start position of the triangle.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, route learning was also found to be enhanced with the use of large displays. Patrick et al (2000) verbally instructed their participants to go from one ride to another in a virtual amusement park along a fixed route. Participants in the large-screen condition were more accurate than participants in the monitor condition when asked to reproduce the map of the amusement park.…”
Section: Discussionmentioning
confidence: 99%
“…Mizell et al find that immersive displays can better convey the sense of space than desktop displays [16]. Patrick et al [20] compare various displays which occupy comparable visual angles, and find that, while users performed significantly worse in forming cognitive maps on a desktop monitor, users performed no differently using a head-mounted display or a large projection display. Similarly, Tan et al [34] studied the effect of large projected wall displays, and suggest that large displays afford a greater sense of presence, leading to better performance.…”
Section: Display Effectsmentioning
confidence: 99%
“…This problem is brought into focus when we consider that some tasks which involve panoramic video imagery are performance critical, such as rescue services telepresence or security surveillance review. One field that has investigated the question of display effect is virtual reality, where it is suggested that immersive displays, such as headmounted displays (HMD), may improve user performance in tasks that require a high level of spatial reasoning [20,16,34]. However, these works often use 3D virtual environments, and panoramas are not 3D: on a spectrum between 3D virtual environments and 2D images, panoramas are a hybrid in between -a 360 • panorama can surround a user, but the scene has only spherical geometry and is effectively flat.…”
Section: Introductionmentioning
confidence: 99%
“…It is also quite difficult to find a balance between display quality and ergonomics, since most systems vary from high quality cumbersome displays to low quality ergonomic ones (Bimber et al, 2006). Another issue related to HMD is the incidence of simulator sickness during fast head movements (Patrick et al, 2000).…”
Section: Head-mounted Displays (Hmds)mentioning
confidence: 99%